Assessing Environmental Literacy: Comparative Analysis of Students in Environment-Focused and General Junior High Schools in Balikpapan - Salsabila, Zulfa; Sholeh, Muhammad; Sulaeman, Nurul Fitriyah; Junus, M; Nuryadin, Atin (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2024)
The Adiwiyata program seeks to cultivate knowledge and awareness of ecological conservation among students. This study compared environmental literacy between ninth-grade students in Adiwiyata and non-Adiwiyata schools in Balikpapan City, Indonesia. Utilizing a questionnaire adapted from the Middle Schools Environmental Literacy Survey, data was collected across five domains: knowledge, attitudes, participation, awareness, and skills. An independent sample t-test gauged mean variations in both school types. Results indicated that Adiwiyata students achieved good environmental literacy, while non-Adiwiyata students reached an acceptable level. Noteworthy differences were observed across all domains, with the knowledge domain being particularly distinct. Strengthening environmental literacy requires schools to implement programs reinforcing environmental values. This study underscores the importance of educational initiatives fostering a sense of responsibility for the environment among students in both Adiwiyata and non-Adiwiyata schools.